Feminism and suffrage : the emergence of an independent women's movement in America, 1848-1869 - DuBois, Ellen Carol, 1947- (Cornell University Press, 1999)
In the two decades since Feminism and Suffrage was first published, the increased presence of women in politics and the gender gap in voting patterns have focused renewed attention on an issue generally perceived as nineteenth-century. For this new edition, Ellen Carol DuBois addresses the changing context for the history of woman suffrage at the millennium.